2020
DOI: 10.3390/w12051231
|View full text |Cite
|
Sign up to set email alerts
|

Framework, Procedure, and Tools for Comprehensive Evaluation of Sustainable Stormwater Management: A Review

Abstract: To better evaluate and enhance the performance and benefit of sustainable stormwater management (SSWM) in developing countries, this study proposes a comprehensive evaluation framework based on thorough literature review. This framework re-classifies evaluation goals and indicators into four aspects—stormwater system, integrated management, social engagement, and urban development. The purpose of this review is to provide a guideline for decision makers to choose appropriate goals and indicators according to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 106 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…According to general stormwater goals (See Table 2), GSI cases [68][69][70][71], and functional specifications of selected WSUD (See Appendix A), 10 sub-criteria and several indicators from functional, economic, social, and environmental variables were determined and shown in Figure 5. The rationale for each sub-criterion and indicator is as follows.…”
Section: Criteria and Indicator Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to general stormwater goals (See Table 2), GSI cases [68][69][70][71], and functional specifications of selected WSUD (See Appendix A), 10 sub-criteria and several indicators from functional, economic, social, and environmental variables were determined and shown in Figure 5. The rationale for each sub-criterion and indicator is as follows.…”
Section: Criteria and Indicator Selectionmentioning
confidence: 99%
“…In fact, there are several good attempts of combining stormwater management and MCDA to score, rank, and select the optimal option by a more generalizable framework. At the theoretical level, Jayasooriya et al [47] Sapkota et al [98], Sapkota et al [46], and Wu et al [71] reported that the establishment of a standard comprehensive assessment framework for GSI is significant and it can further assist decision-makers to make a more reasonable, inclusive, and well-informed decision. At the practical level, Morales-Torres et al [48] reported a decision supported tool called E2STORMED based on MCDA method to assess the multi-benefits of different GSI, and Kuller et al [31] also developed a rapid GSI-based MCDA tool for WSUD assets (called SSANTO), to assist stakeholders engaged in the urban planning in focusing on opportunities and needs of WSUD.…”
Section: Recommendations and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanization processes have also led to the disappearance of many forms of natural water infrastructure, and the dangerous effects of storms and floods are exacerbated by climate change. Commonly used forms of water discharge into stormwater drainage systems lead to an increase in the water deficit in cities [7]. The degradation of sewage systems [8][9][10] and their inefficiency make them ineffective in the event of torrential rains, and they also disrupt hydrological cycles, which is detrimental to the shaping of urban environments and the people living in them [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, quantitative decision support tools have been developed with the main aim to maximize GSI performance to control runoff and water pollution and to be costeffective [48][49][50][51][52]. On the other hand, despite the extensive attempts made to expand the assessment work to include the social aspect of decision support [17,48,[53][54][55][56][57][58][59][60][61][62][63][64], they lack a deeper understanding of the public perceptions and associated cognitive bias perspective to resolve the implementation dilemma from a bottom-up approach [65] as examined in other environmental issues [43,44]. This shortcoming can affect the expected outcomes envisioned by major decision-makers [42,66].…”
Section: Introductionmentioning
confidence: 99%